Efficacy and toxicity profile of pegylated liposomal doxorubicin in patients with advanced ovarian cancer - Mayer, Christine; Brucker, Janina; Schütz, Florian; Domschke, Christoph; Bechstein, Sarah; Heil, Jörg; Golatta, Michael; Wallwiener, Markus; Sohn, Christof; Schneeweiss, Andreas; Rom, Joachim (Archives of gynecology and obstetrics, 2015)
BackgroundThe prognosis of patients with non-platinum-sensitive recurrent ovarian cancer is poor. There is a need for salvage therapies with anti-tumor activity and acceptable toxicity for maintaining quality of life. Pegylated liposomal doxorubicin (PLD, Caelyx®) is a promising drug fulfilling these demands. We present retrospective data of patients with advanced epithelial ovarian cancer (EOC) who were treated with pegylated liposomal doxorubicin at the University of Heidelberg between 2007 and 2009.Patients and methodsEligible patients for this retrospective study had advanced ovarian cancer and were treated in a palliative setting with PLD at the university hospital of Heidelberg, Germany. Primary objectives were toxicity and efficacy of PLD. 34 patients were included in this study between November 2007 and December 2009; one patient received PLD twice as palliative treatment.ResultsThe median age of the 34 patients enrolled in this study was 59.9 years (range 27-77 years). The median weight of the patients was 69 kg (range 47-109 kg), the median height 164 cm (range 140-176 cm). Pegylated liposomal doxorubicin was administered every 4 weeks with a dosage of 40 mg/m2 body surface. PLD was administered for three cycles in median (range 1-9 cycles). Dose reduction was necessary in only four patients. In our study time to progression and overall survival was 8.74 and 14.23 months.ConclusionsIn conclusion, this retrospective study showed the efficacy and low toxicity of pegylated liposomal doxorubicin in patients with advanced EOC. Further observations are needed to confirm these preliminary experiences on a larger number of patients.